1992
DOI: 10.1021/j100182a082
|View full text |Cite
|
Sign up to set email alerts
|

Mutual diffusion coefficients in the water-rich region of water/phenol mixtures and their relation to aggregate formation

Abstract: 1475repulsions between the charged carboxylic groups and results in the formation of mixed micro domain^.'^^ Effect I11 should bring about a decrease of 11/13 but would occur only in PSX solutions with X 2 4.Obviously, for PS1 and PS2 the changes of 11/13 are essentially due to effect I. The decreases of 11/13 in the presence of PS1 or PS2 are only slightly less steep than in pure water. A partial recoiling of the copolymer (effect 111) would have no impact on the change of 11/13, as pyrene is not bound by PS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
6
9
1
Order By: Relevance
“…With sequential injections the average diffusion coefficient obtained was 9.34610 -10 (RSD 0.71%). The obtained diffusion coefficients were repeatable and they agreed well with the values reported in the literature (reference D: 9.4610 -10 m 2 /s) [30]. In the study of the effect of the sample concentration on the measured diffusion coefficients it was found that, at lower concentrations (1 lg/ mL), the peak shapes were poor owing to poor signal to noise ratio.…”
Section: Diffusion Coefficientssupporting
confidence: 88%
“…With sequential injections the average diffusion coefficient obtained was 9.34610 -10 (RSD 0.71%). The obtained diffusion coefficients were repeatable and they agreed well with the values reported in the literature (reference D: 9.4610 -10 m 2 /s) [30]. In the study of the effect of the sample concentration on the measured diffusion coefficients it was found that, at lower concentrations (1 lg/ mL), the peak shapes were poor owing to poor signal to noise ratio.…”
Section: Diffusion Coefficientssupporting
confidence: 88%
“…We note first that our simulated data for phenol in the bulk solution are in good agreement with the experimental data of Castillo et al (1992). At infinite dilution, they obtained values of 9.4 × 10 −10 m 2 s −1 and 1.88 × 10 −9 m 2 s −1 at 296 and 342 K, respectively.…”
Section: Resultssupporting
confidence: 87%
“…This structural picture is consistent with the interpretation of computer simulations (Jorgensen & Nguyen, 1993; Jorgensen et al , 1993). The diffusion coefficients of phenol in the water‐rich regime have been measured with the Taylor dispersion technique (Castillo et al , 1992). At infinite dilution, values of 0.94 × 10 −9 m 2 s −1 and 1.88 × 10 −9 m 2 s −1 are recorded at 296 and 342 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusivity of PhOH in water is calculated as D aq = 9.4 Â 10 À10 m 2 s À1 using the Wilke-Chang equation [50]. Therefore, the thickness of the aqueous boundary layer is calculated as d aq = D aq D aq = 7.74 Â 10 À5 m.…”
Section: Kinetic Modeling Of Phoh Permeationmentioning
confidence: 99%